Prediction of salt contamination on high voltage insulators in rainy season using regression technique - S. Ahmad, Ahmad; Ahmad, Hussein; Salam, Md. Abdus; Tamsir, T; Buntat, Z; Mustafa, M. W. (2000)

(untitled)
The severity of contamination on the high voltage insulator surfaces is the significant factor in determining the level of outdoor insulation and in choosing the types of insulators. In the equatorial region, the most dangerous kind of contamination is salt contamination. A regression technique has been used to develop a modified equivalent salt deposit density (ESDD) mathematical model with respect to meteorological conditions. This model provides a useful way for predicting contamination level and for determining frequency of washing the insulators in a given contaminated area